THE CURRENT STATE OF BUCKWHEAT MARKET IN UKRAINE - Averchev Olexander; Kyrylov Yurii; Fesenko Hanna (Scientific Journal of Pedagogy and Economics, 2021)
The purpose of the article is to study the current state of buckwheat market in Ukraine and the world. Dynamics of buckwheat growing in 2015, 2016, 2017, 2018 and its impact on the domestic and foreign buckwheat market in Ukraine are analyzed. The research is based on the statistics of the State Statistics Committee of Ukraine. The analysis of the buckwheat origin and the area of its growing in the world is conducted. It is established that buckwheat is grown both in Eurasia and America. In Europe, Asia and America, buckwheat is gaining in popularity every year. Due to the fact that this crop is used not only for food and feed purposes, it is also a valuable medicinal plant and a good honey plant. It is proved that Ukraine has all the necessary economic, natural and agro-climatic conditions for the buckwheat growing and not only to satisfy the internal market but also to be a leader among exporters in sales of this crop and products of its processing. It is established that a significant decrease in the buckwheat-growing areas has been observed in recent years, which leads to a decrease in the gross output of the crop. This situation contributes to the rise in retail prices of buckwheat and the loss of positions in the foreign market as a leading exporter in the world.